Review of dengue trend in Kelantan using R programming / Nor Farisha Muhamad Krishnan ... [et al.] - Muhamad Krishnan, Nor Farisha; Ahmad Zulkarnain, Zuriani; Jamaludin, Marhainis; Abdul Rahman, Noorihan (Unit Penerbitan UiTM Kelantan, 2021)
Dengue is an illness transmitted by mosquitoes, causing sudden high fever, severe headache, rashes, muscle and joint pain, pain behind the eyes, and bleeding, in some cases. In Malaysia, dengue has become one of the major problems since it leads to serious dengue fever. This study is done in Kelantan to review the trend in dengue cases from January 2015 to October 2019. The year 2016 has the highest dengue cases compared to other years. Data were obtained from the Department of Health in Kelantan for the year 2015 until 2019. The socio-demographic analysis showed that males (51%) are prone to dengue fever compared to females (49%). Based on ethnicity, Malays (96.38%) have the highest reported dengue cases followed by Chinese, Indian, and others (2.68%, 0.2%, and 0.74%, respectively). Dengue cases were stated higher in the urban area (39.06%) than in rural areas (32.08%). R programming is used to show the trend of the dengue cases and data visualization. The result showed that at early and end of the year, more dengue cases were reported. Thus, effective and efficient strategies, as well as immediate actions for dengue prevention are needed in Kelantan.